Corporate image of Kazzponic Sdn Bhd / Mohd Zuraffly Md Zuki - Md Zuki, Mohd Zuraffly (Faculty of Business and Management, 2009)
Researcher have choose Corporate Image of Kazzponic Sdn Bhd as the topic due to certain issues concerning on Kazzponic’s corporate image towards its company. The objective of this study is to monitor the corporate image management as the key strategy for a competent corporate image of Kazzponic Sdn Bhd. The purpose of this paper is to study and view on Kazzponic Sdn Bhd’s Corporate Image which responds towards heightened concerns in attracting consumers and other marketing channels toward its company and products. Researcher has signaled the need for corporate image in order to build strong brand image so that this company can compete with other competitors which are in the same field. Given this sea change in the corporate environment, companies want to increase their ability to manage their profits and risks, and to protect the reputation of their brands.